Peningkatan Kapasitas Aparat Desa dan Masyarakat dalam Perencanaan Pembangunan - Jumiati Ilham; Ervan Hasan Harun; Arfan Utiarahman (ELDIMAS: Jurnal Pengabdian Pada Masyarakat, 2023)
The implementation of the Community Service Program – Building Villages this time is an integrated Community Service program with Merdeka Learning - Merdeka Campus activities which will be recognized as 20 credit hours of academic activities and spread over several courses, both contained in the curriculum and freeform courses. Based on the results of an assessment of community needs, a list of inventory problems, and a list of the potential that exists in Pontolo village, the KKN MBKM – Building Villages in 2022 has proposed 3 (three) core programs to the village government and have received approval, namely: 1). Microsoft Excel Training and Preparation of Work Unit Price Analysis (AHSP) in accordance with the Indonesian National Standard (SNI); 2). Dissemination and repair of good and safe electrical installations, and 3). UMKM training. The KKN MBKM Program – Building Villages in 2022 in Pontolo village, Mananggu sub-district, Boalemo district has produced: 1). Village officials who have skills in operating Microsoft Excel and are also able to prepare a Cost Budget Plan (RAB) based on Work Unit Price Analysis (AHSP) in accordance with the Indonesian National Standard (SNI); 2). Community groups who have knowledge and skills in making good and safe electrical installations based on and as many as 43 housing units have been successfully reinstalled (reinstalled) based on the General Guidelines for Electrical Installation (PUIL); and 3. Community groups who have knowledge in developing UMKM.